DISC1 and Striatal Volume: A Potential Risk Phenotype For mental Illness - Chakravarty, M. Mallar; Felsky, Daniel; Tampakeras, Maria; Lerch, Jason; Mulsant, Benoit; Kennedy, James; Voineskos, Aristotle (Frontiers in Psychiatry, 2012)
Disrupted-in-schizophrenia 1 was originally discovered in a large Scottish family with abnormally high rates of severe mental illness, including schizophrenia, bipolar disorder, and depression. An accumulating body of evidence from genetic, postmortem, and animal data supports a role for DISC1 in different forms of mental illness. DISC1 may play an important role in determining structure and function of several brain regions. One brain region of particular importance for several mental disorders is the striatum, and DISC1 mutant mice have demonstrated an increase in dopamine (D2) receptors in this structure. However, association between DISC1 functional polymorphisms and striatal structure have not been examined in humans to our knowledge. We, therefore hypothesized that there would be a relationship between human striatal volume and DISC1 genotype, specifically in the Leu607Phe (rs6675281) and Ser704Cys (rs821618) single nucleotide polymorphisms. We tested our hypothesis by automatically identifying the striatum in fifty-four healthy volunteers recruited for this study. We also performed an exploratory analysis of cortical thickness, cortical surface area, and structure volume. Our results demonstrate that Phe allele carriers have larger striatal volume bilaterally (left striatum: p=0.017; right striatum: p=0.016). From the exploratory analyses we found that Phe carriers also had larger right hemisphere volumes and right occipital lobe surface area (p=0.014) compared to LeuLeu homozygotes (p=0.0074). However, these exploratory findings do not survive a conservative correction for multiple comparisons. Our findings demonstrate that a functional DISC1 variant influences striatal volumes. Taken together with animal data that this gene influences D2 receptor levels in striatum, a key risk pathway for mental illnesses such as schizophrenia and bipolar disorder may be conferred via DISC1’s effects on the striatum .